Óxido de ítrio e alumínio dopado com Yb³+ e Er³+ incorporado em membrana de poliamida - Souza, Michel Lucas de (2018)
Lanthanides ions presents intrinsic features such as the light emitting process and these emissions can be governed by downshifting and up-conversion mechanisms. Bioassay has been an example of up-conversion phenomena application due to its infrared excitation possibility which does not excite natural biological molecules and it doesn’t interferes on the detection. In this present work, the yttrium aluminum oxide doped with Yb3+ and Er3+ was synthesized by non-hydrolytic sol gel method using the metal chloride as the precursors. The doped matrix was incorporated and dispersed into a polyamide membrane obtained by Additive Manufacturing. X-ray diffraction analysis showed the formation of the phase’s mixture, mainly the YAM (yttrium aluminum monoclinic). Infrared spectroscopy showed vibration modes at 810 and 448 cm-1 , assigned respectively to AlO6 and AlO4 and at 530 cm-1 to the Y-O bond. The emission spectra with excitation at 980 nm and with different laser power showed that the emission intensities increase as a function of the power. The intensities of the bands corresponding to the transitions 4S3/2 → 4 I15/2 (563 nm) and 5F9/2 → 4 I15/2 (660 nm), showed a two-photon absorption mechanism. The same spectroscopic behavior was observed for the matrix incorporated to the polyamide membrane, that additionally presented a good thermal resistance against the high laser potency when coated with the polyetherimide polymeric film.